Association of Dupilumab with Intraocular Inflammation. (4th July 2022) - Padidam, Sneha; Raiji, Veena; Moorthy, Ramana; Oliver, Armando; Do, Brian
ABSTRACT: Purpose: To report four cases of uveitis after treatment with dupilumab for atopic dermatitis. Methods: Retrospective case series. Results: Data was collected from four patients with inflammation that developed after treatment with dupilumab. The first patient was thought to have developed posterior scleritis or Harada's-type disease related to her treatment with dupilumab, with recurrence of intraocular inflammation upon restarting treatment. The second patient developed anterior and intermediate uveitis as well as cystoid macular edema in her right eye about two years after starting dupilumab treatment. The third patient developed a distinct relentless placoid chorioretinitis while on therapy with dupilumab. The fourth patient developed bilateral cystoid macular edema while on treatment with dupilumab. Conclusion: We report a case series of patients treated with dupilumab who developed intraocular manifestations of inflammatory disease.